The politics of language : conflict, identity and cultural pluralism in comparative perspective - Schmid, Carol L. (Oxford University Press, 2001)
This volume surveys and analyzes the historical background of recent controversies over language in the US, and compares the country to two official multilingual societies: Canada and Switzerland.;This book should be suitable for courses in linguistics, political science, and sociology. It is intended for undergraduate students and graduate students interested in the relationship between language and race, ethnic relations, and political sociology.